2005
DOI: 10.2134/jeq2005.343er
|View full text |Cite
|
Sign up to set email alerts
|

Radioactive Materials in Biosolids

Abstract: past experience, there have been concerns that radioactive materials could concentrate in sewage sludge and The Nuclear Regulatory Commission (NRC) announced the availash and pose a threat to the health and safety of POTW ability of three new documents concerning radioactive materials in sewage sludge and ash from publicly owned treatment works (POTW). workers or the general public. One of the documents is a report presenting the results of a volunteer As a result of interest from the U.S. Congress, the survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…One previous relevant study on this field is Bastian et al (2005) giving information about 311 sewage sludge samples from WWTPs located in the United States and 35 sewage sludge ash samples, where 44 different radionuclides from diverse origins (natural and artificial) were found. In the review from Fonollosa et al (2015) a total of 28 radionuclides were found in the sludges from the different DWTPs studied.…”
Section: Radionuclides In the Urban Water Cyclementioning
confidence: 99%
See 2 more Smart Citations
“…One previous relevant study on this field is Bastian et al (2005) giving information about 311 sewage sludge samples from WWTPs located in the United States and 35 sewage sludge ash samples, where 44 different radionuclides from diverse origins (natural and artificial) were found. In the review from Fonollosa et al (2015) a total of 28 radionuclides were found in the sludges from the different DWTPs studied.…”
Section: Radionuclides In the Urban Water Cyclementioning
confidence: 99%
“…A relevant study about the presence of radionuclides in WWTPs is Fischer et al (2009) which reported the presence of medically-derived 99m Tc and 131 I in wastewater, sludges, sewage effluent and in sediments. Although some studies reported levels of medically-derived radionuclides in WWTPs (Barci-Funnel et al, 1993;Dalmasso et al, 1997;Bastian et al, 2005;Rose et al, 2012;Punt et al, 2007;Fenner and Martin 1997;Montaña et al, 2013a;Barredo 2010;Chang et al, 2011;Mc Gowan et al, 2014;Martínez et al, 2018), very few studies have gone one step beyond and identify relationships of the levels found with other factors (Zannonni et al, 2018;Hormann and Fischer 2018).…”
Section: Medically-derivedmentioning
confidence: 99%
See 1 more Smart Citation